(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
This article provides information on the etiology, pathogenesis, clinical signs, methods of diagnosis of uterine diseases-endometritis, which are common among dairy cows in livestock farms, and recommendations for treatment and prevention are given